THE INFLUENCE OF FOOD INFLUENCERS ON CULINARY PURCHASE INTENTION - Azis, Saipul; Habibi, Roihan; Supriyadi, Ilham; Ikhsan, Ainul; Akbar, Anton; Candra, Dul (Journal of Management and Islamic Finance, 2025)
This study aims to analyze the influence of food influencers in Padang, specifically examining three credibility dimensions: attractiveness, trustworthiness, and expertise, on consumer purchase intention in the culinary sector. This research is motivated by the importance of understanding influencer effectiveness in the digital era, which is driven by "instant gratification," particularly in a region with a rich culinary heritage like Padang. This study fills a gap in the literature, as specific research on this topic in Padang remains limited. The research employs a quantitative approach with a causal-associative design. Primary data were collected through an online questionnaire (Google Forms) distributed to 150 respondents with criteria requiring respondents to be familiar with Padang cuisine, have seen food influencer content, and be over 17 years old. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 4.1.1.4 software. The findings indicate that trustworthiness (p=0.002) and expertise (p=0.000) have a significant positive influence on purchase intention. Expertise was identified as the most influential factor. Conversely, the study found that an influencer's attractiveness (p=0.477) has no significant influence in the context of Padang culinary products. The structural model demonstrated high predictive relevance (Q² = 0.522). Theoretically, this research contributes to the source credibility literature by demonstrating that for experiential products like cuisine, consumers value substantive credibility cues (knowledge and trust) over peripheral cues (physical appearance). From a managerial perspective, culinary entrepreneurs in Padang are advised to prioritize collaborations with influencers perceived as authentic and knowledge.